Pragmalinguistic Aspects of English Dialogic Speech - Sabiya Nuridinova Alahiddinovna (International Journal on Integrated Education, 2023)
The aim of the article is determined by the fact that the appeal to various social, psychological, personal, and individual characteristics of a person is of particular interest for research in the field of linguistics, psycholinguistics, sociolinguistics, and ethnolinguistics related to the human factor.